Curriculum theory: Empowering teachers in delivering effective teaching for children’s holistic development - Idowu Tope Aisha Adekanbi; Michael Timilehin Oladele (Curricula: Journal of Curriculum Development, 2024)
The significance of curriculum in education cannot be underestimated, as it enables teachers to know what to teach during teaching and learning. The dominant curriculum used in schools today is a scripted curriculum that does not allow teachers to see learners as co-creators in constructing knowledge. Many teachers find it challenging to adjust this curriculum to the interests and abilities of learners. This article aims to explore how scripted curricula can be adapted in childhood education to promote a child-centered approach that acknowledges children's knowledge, interests, needs, and abilities. This article examines 2011 to 2024 peer-reviewed articles that emphasize curriculum flexibility and students’ involvement in creating knowledge with 104 articles. The findings show that teachers need the knowledge of curriculum theory to modify and implement scripted curriculum in a way that is inclusive and culturally responsive to all learners. This knowledge will enable teachers to deliver instruction capable of motivating learners to work at their own pace and participate in meaningful and rewarding learning experiences.   Abstrak Pentingnya kurikulum dalam pendidikan tidak dapat diremehkan, karena kurikulum memungkinkan guru untuk mengetahui apa yang harus diajarkan selama proses belajar mengajar. Kurikulum dominan yang digunakan di sekolah saat ini adalah kurikulum tertulis yang tidak memungkinkan guru untuk melihat peserta didik sebagai rekan pencipta dalam membangun pengetahuan. Banyak guru merasa sulit untuk menyesuaikan kurikulum ini dengan minat dan kemampuan peserta didik. Tujuan artikel ini adalah untuk mengeksplorasi bagaimana kurikulum tertulis dapat diadaptasi dalam pendidikan anak usia dini untuk mempromosikan pendekatan yang berpusat pada anak yang mengakui pengetahuan, minat, kebutuhan, dan kemampuan anak-anak. Artikel ini mengkaji artikel yang ditinjau sejawat dari tahun 2011 hingga 2024 yang menekankan fleksibilitas kurikulum dan keterlibatan siswa dalam penciptaan pengetahuan menggunakan 104 artikel. Temuan menunjukkan bahwa pengetahuan teori kurikulum dibutuhkan oleh guru untuk memodifikasi dan menerapkan kurikulum tertulis dengan cara yang inklusif dan responsif secara budaya terhadap semua peserta didik. Pengetahuan ini memungkinkan guru untuk memberikan instruksi yang mampu memotivasi peserta didik untuk bekerja sesuai kecepatan mereka sendiri dan berpartisipasi dalam pengalaman belajar yang bermakna dan bermanfaat. Kata Kunci: kurikulum tertulis; minat peserta didik; praktik pembelajaran; teori kurikulum